Comparative evaluation of enamel remineralization potential of processed cheese, calcium phosphate-based synthetic agent, and a fluoride-containing toothpaste: An in situ study - Navneet Grewal; Samita Gumber; Nirapjeet Kaur (Wolters Kluwer Medknow Publications, 2017)
Background: Enamel remineralization potential of variety of products has been established, but there is a lack of evidence of comparison of remineralization potential of natural versus synthetic products. Aim: The aim of this study was to compare the enamel remineralization potential of saliva, cheese, casein phosphopeptide-amorphous calcium phosphate (CPP-ACP)-based synthetic agent, and fluoride toothpaste. Design: In situ study was carried out on sixty individuals who wore an intraoral appliance containing demineralized enamel slabs for each agent. One out of six slabs was kept as a control so as to record the baseline values (neither subjected to demineralization nor remineralization). Experimental agents were applied on the designated enamel slabs on day 1, 4, 7, and 10 with a crossover wash out period of 7 days. Quantitative values of mineral content of slab were measured using energy dispersive X-ray and qualitative changes in surface topography of slab were seen under scanning electron microscope at ×20K magnification. Results: Highly significant changes from baseline values were seen in calcium and phosphorus content of slabs treated with cheese and CPP-ACP-based agent whereas levels of fluoride were significantly higher in enamel slabs treated with fluoride-containing toothpaste. Conclusion: Cheese is an organic, economical, and user-friendly option over prescribed synthetic agents. A synergistic effect of fluoride-containing toothpaste with intake of cheese could be a good enamel remineralization protocol.